Hydrogenation of Cinnamaldehyde by Water‐Soluble Ruthenium(II) Phosphine Complexes: A DFT Study on the Selectivity and Viability of trans‐Dihydride Pathways. Issue 3 (29th December 2020) - Fehér, Péter Pál; Joó, Ferenc; Papp, Gábor; Purgel, Mihály
Abstract: Apart from the important trans ‐dihydrido‐transition metal catalysts containing polydentate phosphine, diamine or pincer‐type ligands, the catalytic role of trans ‐dihydride complexes with monodentate ligands is generally neglected given their inferior thermodynamic stability compared to the cis isomers. This way however, a mechanistic investigation about selectivity loses important details as more prominent catalysts provide multiple competing pathways towards the desired product. Here, we used the hydrogenation of cinnamaldehyde as model reaction to gain theoretical insight about whether the water soluble ruthenium trans‐dihydride complexes, trans ‐[Ru(II)H2 P3 L] (P=PPh3 in the model, monosulfonated PPh3 ( m tppms) in experiments, L=H2 O or P), are, indeed, feasible catalytic species as suggested on the basis of experimental investigations. After evaluating numerous catalytic cycles, we found that the consideration of thermodynamically accessible trans ‐dihydrides provides two viable competing reaction channels. The key feature of the mechanisms is the inclusion of explicit solvent (water) molecules, which allows the separation of substrate hydrogenation from the rate determining catalyst regeneration, where the H−H activation occurs. We found that the former determines the selectivity towards carbonyl hydrogenation through the more favorable hydride transfer to the carbonyl carbon. Abstract : The known active hydrogenation catalysts based on trans ‐dihydrido metal complexes contain bi‐ or polydentate, often pincer‐type ligands. In the present work, DFT calculations reveal the often overlooked but potentially important role of trans ‐Ru(II)‐dihydrides with monodentate ligands in regioselective catalytic hydrogenation of cinnamaldehyde to the corresponding allylic alcohol.